ESG reporting and financial performance in Nigeria’s telecommunications sector - Herbert, Wilson E.; Uzah, Cheta K.; Agwor, ThankGod C. (Journal of Accounting, Business and Finance Research, 2026)
This study explores the relationship between ESG Reporting (ESGR) and financial performance (FP) in Nigerian telecommunications companies listed on the Nigerian Exchange Group (NGX). Using panel data from 2017 to 2023 and a Random Effects Model (REM), the research examines the impact of carbon emissions (CE), employee diversity (ED), and board composition (BC) on FP. Results indicate that CE have a negative effect on FP, while ED positively influences it. Although the effect of BC on FP is not significant, the study suggests investing in cleaner technologies, promoting employee diversity, and increasing board representation to enhance financial performance and mitigate environmental risks. Telecom companies can reduce their carbon footprint by adopting renewable energy and sustainable practices. Improving diversity metrics and financial results can further enhance the impact of employee diversity on financial performance. Challenges such as cultural biases and regulatory obstacles may impede board diversity in Nigeria’s telecom sector. The study provides insights and recommendations on ESGR for policymakers, regulators, and investors in developing economies to achieve a balance between sustainability and financial growth.